Nilai - Nilai Pendidikan Islam pada Kesenian Tari Rampak Barongan Sanggar Seni Krido Turonggo Mudo di Kelurahan Koya Barat Kota Jayapura - Muhammad Rouf Asrovy (Reflection : Islamic Education Journal, 2026)
This study aims to identify and describe the values of Islamic education embedded in the art of Rampak Barongan Dance performed by the Krido Turonggo Mudo Art Studio in Koya Barat Subdistrict, Jayapura City, as well as to analyze this artistic practice as a medium for character education and cultural da’wah within the community. This research employs a qualitative method with a descriptive approach, focusing on an in-depth understanding of the meanings and practices of Islamic values in artistic activities. Research data were collected through direct observation, in-depth interviews with the studio managers and members, and documentation related to the dance training and performance processes. The collected data were analyzed interactively through the stages of data reduction, data display, and conclusion drawing to obtain systematic and comprehensive results. The findings indicate that the Rampak Barongan Dance contains Islamic educational values, including faith (aqidah), sharia, morality (akhlak), and social values. These values are reflected in prayers before performances, the use of modest attire in accordance with Islamic sharia, sincerity in performance, social ethics, solidarity, and teamwork. The practice of training and performing the dance serves as a means of cultivating discipline, responsibility, respect for time, and functions as an effective medium of cultural da’wah by integrating artistic aesthetics with Islamic moral messages.